The Development of Cabe Gemoi Teaching Module (Communicate, Empathize, Cooperate, and Manage Emotions) Integrated SEL in Science Learning in Satu Atap 6 Menthobi Raya Junior High School - Maryadi Henyatno; Bulkani Bulkani; Tazkiyatunnafs Elhawwa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Background: It is necessary to develop teaching modules involving SEL for junior high school students, so this study innovates by developing SEL-based teaching modules. Aim: (1) describe the process of developing the Cabe Gemoi teaching module for ninth-grade students at Satu Atap 6 Menthobi Raya Junior High School; (2) test the feasibility of the Cabe Gemoi teaching module for ninth-grade students at Satu Atap 6 Menthobi Raya Junior High School; (3) test the practicality of the Cabe Gemoi teaching module for ninth-grade students at Satu Atap 6 Menthobi Raya Junior High School; (4) testing the effectiveness of the Cabe Gemoi teaching module in improving communication, empathy, cooperation, and emotion management skills for ninth-grade students at Satu Atap 6 Menthobi Raya Junior High School. Method: This research was a research and development study using the ADDIE model. The respondents in the small-scale test were ninth-grade students at Satu Atap 6 Menthobi Raya Junior High School, and the large-scale test was conducted with ninth-grade students at 2 Menthobi Raya Junior High School. Data collection was carried out using observation, interviews, questionnaires, and documentation. The data were processed by using qualitative and quantitative analysis techniques. Results and Dıscussion: (1) The development process used the ADDIE model, which began with analysis, design, development, implementation, and evaluation. The analysis used observation, questionnaires, and interviews. The design included the design of teaching modules and research instruments. Development used Canva and Microsoft Word and was then tested by experts. Implementation included small-scale and large-scale testing. Evaluation is carried out by testing the effectiveness of the teaching module. (2) The Cabe Gemoi teaching module is considered feasible through expert media validation testing (91.07) in the highly suitable category and subject matter experts (88.04) in the suitable category. (3) The Cabe Gemoi teaching module is considered practical with a score of 87.85 in the suitable category. (4) The Cabe Gemoi teaching module was deemed low effective with a n-gain value 0,29; however, based on students’ score, there is an improvement in attitude and emotional. Conclusion: Cabe Gemoi Teaching Module assisted SEL which was developed for ninth grade students of Menthobi Raya Junior High School can improve how to communicate, empathize, cooperate, and emotion management.